2018
DOI: 10.1016/j.ympev.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the phylogeny of the TMBIM superfamily across the tree of life: Comparative genomics and synteny networks reveal independent evolution of the BI and LFG families in plants

Abstract: The Transmembrane BAX Inhibitor Motif containing (TMBIM) superfamily, divided into BAX Inhibitor (BI) and Lifeguard (LFG) families, comprises a group of cytoprotective cell death regulators conserved in prokaryotes and eukaryotes. However, no research has focused on the evolution of this superfamily in plants. We identified 685 TMBIM proteins in 171 organisms from Archaea, Bacteria, and Eukarya, and provided a phylogenetic overview of the whole TMBIM superfamily. Then, we used orthology and synteny network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…We found that progeny derived from a single asexually-reproducing M. persicae clone O female stably colonizes nine divergent plant species of five families that span the Angiosperm phylogeny (27), demonstrating that M. persicae is truly polyphagous. Because genome annotation pipelines are generally focused on protein-coding genes, the majority Ya family members were not annotated in the first version of the M. persicae genome annotation (22).…”
Section: Discussionmentioning
confidence: 93%
“…We found that progeny derived from a single asexually-reproducing M. persicae clone O female stably colonizes nine divergent plant species of five families that span the Angiosperm phylogeny (27), demonstrating that M. persicae is truly polyphagous. Because genome annotation pipelines are generally focused on protein-coding genes, the majority Ya family members were not annotated in the first version of the M. persicae genome annotation (22).…”
Section: Discussionmentioning
confidence: 93%
“…The global phylogenetic and synteny network analyses generated a robust six-group classification system for ARF genes and indicated pervasive intra-group syntenic phylogenetic relationships. To elaborate the evolutionary processes within each of the six groups, individual phylogenetic trees for angiosperm genes in each of the six groups were estimated separately and syntenic connections within each network community were mapped onto the six gene trees (Gamboa-Tuz et al , 2018). Along with the ARF geness identified from Phytozome plant genomes, the ARF genes from basal angiosperms (also ANA grade) and magnoliids were incorporated in the phylogenetic analyses, however these ARF gene sequences were derived from transcriptomes and thus did not provide syntenic information.…”
Section: Resultsmentioning
confidence: 99%
“…Mammals possess six TMBIM subtypes (TMBIM1-6) (Hu et al ., 2009; Rojas-Rivera and Hetz, 2015). Only two subtypes, GAAP (LFG4/TMBIM4) and BI-1 (TMBIM6), are conserved in plants but several plant species show an intriguing expansion of the GAAP protein family (Gubser et al ., 2007; Gamboa-Tuz et al ., 2018). The Arabidopsis, rice ( Oryza sativa ) and the basal angiosperm Amborella trichopoda genomes contain five, seven and two putative GAAP s, respectively (Figure 1).…”
Section: Resultsmentioning
confidence: 99%